Relaciones entre Chile y Japón : un siglo de acercamiento - Andraca, Roberto de (Estudios Internacionales, 2006)
This work recounts the Japanese modernization process from the 19th century to later detail the close relationship of this nation with Chile. We argue that Japan, in its ancient agony and modernization drama, saw a similar image of itself in Chile. In this case, a young but thriving country that conquered and expanded with just titles. Japan learned about Chile and defined it according to its feelings, as a country led by a strong, sovereign government, which led a fierce and at the same time pious people, with whom it maintained a friendly relationship for more than a century, only interrupted by World War II events.